2022
DOI: 10.1302/2046-3758.118.bjr-2021-0576.r1
|View full text |Cite
|
Sign up to set email alerts
|

Tendon healing: a concise review on cellular and molecular mechanisms with a particular focus on the Achilles tendon

Abstract: Tendon is a bradytrophic and hypovascular tissue, hence, healing remains a major challenge. The molecular key events involved in successful repair have to be unravelled to develop novel strategies that reduce the risk of unfavourable outcomes such as non-healing, adhesion formation, and scarring. This review will consider the diverse pathophysiological features of tendon-derived cells that lead to failed healing, including misrouted differentiation (e.g. de- or transdifferentiation) and premature cell senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 141 publications
0
32
0
Order By: Relevance
“…Nevertheless, it should be noted that although the regeneration potential ability of a tendon has been reported in patients with total tendon removal via a surgical procedure, 5,11,14 there was limited healing potential for tendinopathy or tendon rupture. 22,30 One potential reason is probably that the pathologic changes of tendon removal were different from those of tendinopathy in the clinic. Thus, how and when MDCs could participate in tendon repair and healing remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should be noted that although the regeneration potential ability of a tendon has been reported in patients with total tendon removal via a surgical procedure, 5,11,14 there was limited healing potential for tendinopathy or tendon rupture. 22,30 One potential reason is probably that the pathologic changes of tendon removal were different from those of tendinopathy in the clinic. Thus, how and when MDCs could participate in tendon repair and healing remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is not surprising that there was no major difference in the degree of macrophage and FBGC accumulation at either the P(LA-CL) fibers (larger diameter fibers) and PLA with smaller fiber diameters. Immune cells, particularly macrophages, are well known to contribute to tendon healing (Schulze-Tanzil et al 2022) and hence, macrophage polarization has to be considered. ECM components such as collagen (Kajahn et al 2012), but also scaffold material, might influence macrophage polarization from pro-inflammatory M1 to anti-inflammatory M2 type, which is more favorable for healing processes in tendons (Schulze-Tanzil et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells, particularly macrophages, are well known to contribute to tendon healing (Schulze-Tanzil et al 2022) and hence, macrophage polarization has to be considered. ECM components such as collagen (Kajahn et al 2012), but also scaffold material, might influence macrophage polarization from pro-inflammatory M1 to anti-inflammatory M2 type, which is more favorable for healing processes in tendons (Schulze-Tanzil et al 2022). Due to this observation, a cell-mediated fiber degradation should be considered.…”
Section: Discussionmentioning
confidence: 99%
“… 12 The balance between M1 and M2 macrophages is essential for tissue regeneration. 13 Importantly, recent findings have indicated that macrophages exhibit mechanically sensitive characterization and that their polarization state could be regulated by mechanical cues, 14 which may account for load-induced T-B healing.…”
Section: Introductionmentioning
confidence: 99%